2020
DOI: 10.1038/s41436-019-0673-0
|View full text |Cite
|
Sign up to set email alerts
|

The implementation of newborn screening for spinal muscular atrophy: the Australian experience

Abstract: Purpose: To evaluate the implementation of the first statewide newborn screening (NBS) program for spinal muscular atrophy (SMA) in Australia. Processes that hinder and support clinical development, translation, and sustainability of the first primary genetic screening program in Australia are appraised. Methods: The study prospectively describes the course (timelines, health processes, and preliminary clinical outcomes) for SMA screen-positive newborns from 1 August 2018 to 31 July 2019 in New South Wales and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(120 citation statements)
references
References 29 publications
2
91
0
9
Order By: Relevance
“…Preliminary results of the SMA newborn screening program in Australia reported 9 positive cases, but none had 4 SMN2 copies. 37 It is important to highlight that copy number studies in positive patients detected by newborn screening should be performed in expertise centers and with a validated methodology. In the shared decision to immediately start treatment of neonates with 4 SMN2 copies or delay the initiation of treatment, several alternatives-each with advantages and disadvantages-have to be considered (outlined in table 5).…”
Section: Yesmentioning
confidence: 99%
“…Preliminary results of the SMA newborn screening program in Australia reported 9 positive cases, but none had 4 SMN2 copies. 37 It is important to highlight that copy number studies in positive patients detected by newborn screening should be performed in expertise centers and with a validated methodology. In the shared decision to immediately start treatment of neonates with 4 SMN2 copies or delay the initiation of treatment, several alternatives-each with advantages and disadvantages-have to be considered (outlined in table 5).…”
Section: Yesmentioning
confidence: 99%
“…The data from human trials also support the importance of a therapeutic window for a SMN-augmented treatment [60]. Unfortunately, SMA newborn screening programs have not yet been extensively performed worldwide or even nationwide [61,62]. On the other hand, patients with later-onset type 2 SMA showed significant motor improvement after treatment [63]; however, whether the long-term effect will be seen when treatment is initiated in the later SMA phase with slow decline is still unclear [64].…”
Section: Nusinersen: the First Approved Splicing-modify Therapy For Smamentioning
confidence: 89%
“…44 On the other hand, the Australian pilot study reported only patients with 2 and 3 copies. 45 This was to avoid possible psychological harm by providing an early diagnosis with no immediate option for therapeutic intervention due to the reimbursement of nusineresen in Australia only for patients younger than 18 years and with disease onset <3 years. SMA was diagnosed in 9/103,903 newborns (frequency of potential SMA1 and SMA2 1:11545).…”
Section: Risdiplam (Evrysdi)mentioning
confidence: 99%
“…In the previously cited German and Australian pilot studies, attention was drawn to a very narrow therapeutic window for patients with acute SMA. [43][44][45] Four of the nine children identified in the Australian study had symptoms of the disease between 16 and 33 days of life. In one child, the full symptoms of SMA were present on day 16.…”
Section: Patients Diagnosed In Nbs -Too Late or Too Early For Treatment?mentioning
confidence: 99%